2019
DOI: 10.1057/s41599-019-0257-2
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal features of spatial variation in construction land in Beijing (1985–2015)

Abstract: Over the last 30 years, Beijing has experienced rapid development. The city's spatial pattern and changes are extremely complicated. Therefore, to reveal the spatial patterns at different scales and levels, the construction land in Beijing within the 6th ring road in 1985, 1999, 2008, and 2015, was analyzed using global and local multifractal analyses. The global analysis shows that, over the past 30 years, the development of new construction land in this region experienced a process that transformed it from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The research results are once summarized by Batty and Longley (1994) and Frankhauser (1994). Recent years, new progress of studies on fractal cities have been made, and many interesting results were reported in literature (Boeing, 2018;Chen, 2012Chen and Huang, 2019;Lagarias and Prastacos, 2018;Leyton-Pavez et al, 2017;Li et al, 2013;Ma et al, 2020;Man et al, 2019;Purevtseren et al, 2018;Rastogi and Jain, 2018;ShreevastavaRao and McGrath, 2019;Song and Yu, 2019;Tucek and Janoska, 2013;Versini et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…The research results are once summarized by Batty and Longley (1994) and Frankhauser (1994). Recent years, new progress of studies on fractal cities have been made, and many interesting results were reported in literature (Boeing, 2018;Chen, 2012Chen and Huang, 2019;Lagarias and Prastacos, 2018;Leyton-Pavez et al, 2017;Li et al, 2013;Ma et al, 2020;Man et al, 2019;Purevtseren et al, 2018;Rastogi and Jain, 2018;ShreevastavaRao and McGrath, 2019;Song and Yu, 2019;Tucek and Janoska, 2013;Versini et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…The rapid expansion of urban land resulted in an increase in land take per person across the globe in recent decades (Li et al, 2022a). Previous studies on the spatial distribution of urban elements mainly focus on population and urban land (Akbar et al, 2019;Batty, Sik Kim, 1992;Kroll, Haase, 2010;Song, Yu, 2019). In terms of quantitative models describing urban land density spatial patterns, previous studies proposed a linear model with two stages, inverse-S function, and Geographic Micro-Process (GMP) models to describe the spatial distribution of urban land (Guérois, Pumain, 2008;Jiao, 2015;Jiao et al, 2021).…”
mentioning
confidence: 99%